Studi Eksploratif: Pengembangan Modul Fisika SMA/MA Berbasis Framework TPACK - Andi Reski; Nurlayli Hasanah (Universitas Halu Oleo, 2022)
Research has been carried out with the type of exploratory research which aims to identify teaching materials that need to be developed to support physics learning in SMA/MA class X and describe the results of the needs analysis for the development of physics modules for SMA/MA class X based on TPACK. The research method used is quantitative and qualitative research methods with data collection instruments using questionnaires and interview sheets. Furthermore, the sampling technique used in determining the research sample was purposive sampling so that 30 students were selected as the subjects for distributing the questionnaire and 6 students as the interview subjects. Analysis of the data from the results of the distribution of the questionnaire used descriptive statistical analysis while the analysis of data from the results of the interviews was in the form of data reduction, data presentation and drawing conclusions. Based on the results of the study, it is known that teaching materials in the form of modules need to be developed in high school/MA physics learning, especially class X material and as many as 63.3% of students strongly agree to develop a physics module for SMA/MA class X based on the TPACK framework which contains technological knowledge, material, and pedagogy.